Effects of Polyphenols and Lignans of Phyllanthus amarus Schumach. and Thonn. on IL-1β and TNF-α Secretions from LPS-induced THP-1-derived Macrophages - Alam, Javaid; Jantan, Ibrahim; Yuandani; Nafiah, Mohd A.; Mesaik, Muhammed Ahmed; Ibrahim, Sarah (Natural Products Journal, The, 2024)
Background: Phyllanthus amarus exhibited immunosuppressive and anti-inflammatory effects in several in vitro and in vivo studies. However, there is no report on the inhibitory effects of its secondary metabolites on pro-inflammatory cytokines secretion from human THP-1-derived macrophages. Objective: The objective of this study was to correlate the polyphenols (ellagic acid (EA), gallic acid (GA), geraniin (GER), and corilagin (COR)) and lignans (phyllanthin (PHY), hypophyllanthin (HYPO), niranthin (NIR), phyltetralin (PHYLT), and isolintetralin (ISO)) of 80% ethanol extract of P. amarus with their inhibitory effect against IL-1β and TNF-α secretions from LPS-induced THP-1- derived macrophages. Methods: Chemical profiling of P. amarus was carried out by LC-MS/MS analysis. Validated qualitative and quantitative reversed-phase HPLC analyses of the P. amarus extract were performed for the determination of lignan and polyphenol contents. Human THP-1-derived macrophages were prepared by treatment of THP-1 cells with phorbol 12-myristate 13-acetate (PMA). The inhibition of cytokines released by the extract, lignans and polyphenols in the cells was investigated using ELISA assay. Results: P. amarus extract and its chemical constituents significantly reduced the levels of IL-1β and TNF-α in a dose-dependent manner. At a dose of 50 μM, COR exhibited a maximum inhibition of 81.11% on TNF-α secretion, while GER showed 72.56% inhibition on IL-1β secretion. COR demonstrated the strongest inhibition of TNF-α secretion, exhibiting an IC50 value of 9.06 μM, which was comparable to that of dexamethasone (7.07 μM). Meanwhile, GER was the most potent against IL- 1β secretion, exhibiting an IC50 value of 20.09 μM. In the case of TNF-α secretion, the order of potency observed among the active compounds, with regard to IC50 value, was COR > GER > HYPO > PHY > NIR > GA > EA >ISO > PHYLT. For IL-1β secretion, the order of potency was GER > NIR > COR > GA > EA > PHY > HYPO > PHYLT > 1SO. Conclusion: The polyphenol contents of P. amarus, especially COR and GER, contributed significantly to the suppression of cytokines secretion, and they have the potential to be developed into agents for the treatment of pathologic inflammation.
Keywords: Phyllanthus amarus